A Universal Early Parenting Education Intervention in Community-Based Primary Care Settings: Development and Installation Challenges - Grainne Hickey; Sinead McGilloway; Yvonne Leckey; Ann Stokes (MDPI AG, 2018)
Prevention and early intervention programmes, which aim to educate and support parents and young children in the earliest stages of the family lifecycle, have become an increasingly popular policy strategy for tackling intergenerational disadvantage and developmental inequality. Evidence-based, joined-up services are recommended as best practice for achieving optimal outcomes for parents and their children; however, there are persistent challenges to the development, adoption and installation of these kinds of initiatives in community-based primary health care settings. In this paper, we present a description of the design and installation of a multi-stakeholder early parenting education and intervention service model called the Parent and Infant (PIN) programme. This new programme is delivered collaboratively on a universal, area-wide basis through routine primary care services and combines standardised parent-training with other group-based supports designed to educate parents, strengthen parenting skills and wellbeing and enhance developmental outcomes in children aged 0–2 years. The programme design was informed by local needs analysis and piloting to establish an in-depth understanding of the local context. The findings demonstrate that a hospitable environment is central to establishing interagency parenting education and supports. Partnership, relationship-building and strategic leadership are vital to building commitment and buy-in for this kind of innovation and programme implementation. A graduated approach to implementation which provides training/education and coaching as well as organisational and administrative supports for practice change, are also important in creating an environment conducive to collaboration. Further research into the impact, implementation and cost-effectiveness of the PIN programme will help to build an understanding of what works for parents and infants, as well as identifying lessons for the development and implementation of other similar complex prevention and intervention programmes elsewhere. This kind of research coupled with the establishment of effective partnerships involving service providers, parents, researchers and policy makers, is necessary to meeting the challenge of improving family education and enhancing the capacity of family services to help promote positive outcomes for children.